Trading on Time - Djankov, Simeon; Freund, Caroline; Pham, Cong S. (World Bank, Washington, DC, 2012)
The authors determine how time delays affect international trade using newly collected World Bank data on the days it takes to move standard cargo from the factory gate to the ship in 126 countries. They estimate a modified gravity equation, controlling for endogeneity and remoteness. On average, each additional day that a product is delayed prior to being shipped reduces trade by at least 1 percent. Put differently, each day is equivalent to a country distancing itself from its trade partners by 70 kilometers on average. Delays have an even greater impact on developing country exports and exports of time-sensitive goods, such as perishable agricultural products. In particular, a day's delay reduces a country's relative exports of time-sensitive to time-insensitive agricultural goods by 6 percent.